Energy and electron spectra after grazing- ion-surface collisions - Gravielle, Maria Silvia (2002)
For ions that impinge grazing on solid surfaces, binary collisions with the free-electron gas are investigated by means of a modified specular-reflection (MSR) model. The proposed MSR theory is applied to the calculation of the energy lost by fast protons after colliding with an aluminum surface. We also employ the MSR binary theory to study the energy spectra of the emitted electrons. The contribution coming from atomic inner shells, calculated with the continuum-distorted-wake–eikonal-initial-state approximation, is added to the emission probability from the valence band. The total results obtained with the MSR model are in reasonable agreement with available experimental data for 100 keV protons and large ejection angles of the electron. In contrast instead, the usual specular-reflection binary model shows a prominent structure at low electron energies, which greatly overstimates the experimental spectrum.